Post rascom resettlement scheme : an assessment of the present livelihood of resettled Longhouse communities in Nanga Tada, Kanowit, Sarawak - Jesse Merayang, anak John (Universiti Malaysia Sarawak (UNIMAS), 2004)
The New Economic Policy, introduced by the Federal Government, was aimed at eradicating poverty and reorganising to the Malaysian Society so that the economic wealth of the nation would be proportionately distributed among the people. This was conducted by launching several development projects and getting the rural communities to be actively involved in agriculture on a commercial scale. This study is to determine the connection between the current socio-economic status of the NTRS settlers, their livelihood strategies and the impact of natural resource management. The study employed the scientific social-science method of collecting data by means of scheduled interviews, observation and participation with the respondents and then analysing the findings using SPSS Programme. The result of the study shows that the communities involved in the RASCOM resettlement scheme are still behind in their economic activities with unstable income. However, they succeeded in emerging from poverty by earning an income above the PLI. This seems to indicate that government efforts in attempting to eradicate poverty have been successful in Ng Tada communities. Settlers in NTRS realize the importance of the environment in their daily life, including natural resources and the ecosystem. However, further steps to improve the quality of the environment should be pursued. Overall, the settlers would prefer oil palm plantation, fruit orchard and fresh water fishpond projects to be undertaken in the idle land as a priority.